2019
DOI: 10.1158/1078-0432.ccr-19-0475
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Aberrations in the CDK4 Pathway Are Associated with Innate Resistance to PD-1 Blockade in Chinese Patients with Non-Cutaneous Melanoma

Abstract: Purpose: PD-1 checkpoint blockade immunotherapy induces long and durable response in patients with advanced melanoma. However, only a subset of patients with melanoma benefit from this approach. The mechanism triggering the innate resistance of anti-PD-1 therapy remains unclear.Experimental Design: Whole-exome sequencing (WES) and RNA sequencing (RNA-Seq) analyses were performed in a training cohort (n ¼ 31) using baseline tumor biopsies of patients with advanced melanoma treated with the anti-PD-1 antibody. C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 62 publications
0
56
0
Order By: Relevance
“…The effect on tumour growth correlated with decreased phosphorylation of RB Transcriptional Corepressor 1 (Rb1) (Kong et al., 2017). Complementary to these findings, Yu et al (2019) showed that, in humanized mouse and PDX models, palbociclib improved response to immune checkpoint blockade. Although this was not observed specifically in acral melanoma models, supporting evidence suggests that these results may be applied to this melanoma subtype.…”
Section: Disease Models and Potential Therapeutic Treatmentsmentioning
confidence: 84%
See 1 more Smart Citation
“…The effect on tumour growth correlated with decreased phosphorylation of RB Transcriptional Corepressor 1 (Rb1) (Kong et al., 2017). Complementary to these findings, Yu et al (2019) showed that, in humanized mouse and PDX models, palbociclib improved response to immune checkpoint blockade. Although this was not observed specifically in acral melanoma models, supporting evidence suggests that these results may be applied to this melanoma subtype.…”
Section: Disease Models and Potential Therapeutic Treatmentsmentioning
confidence: 84%
“…Oncogenic activation of the CDK4 pathway through copy-number gains in CDK4, CCND1 and loss of CDKN2A is a common genetic feature of acral melanomas (Bastian et al, 2000;Curtin et al, 2005;Furney et al, 2012;Kong et al, 2017;Liang et al, 2017 (Kong et al, 2017). Complementary to these findings, Yu et al (2019) showed that, in humanized mouse and PDX models, palbociclib improved response to immune checkpoint blockade. Although this was not observed specifically in acral melanoma models, supporting evidence suggests that these results may be applied to this melanoma subtype.…”
Section: Is E a S E Model S And P Otential Ther Apeuti C Tre Atmentsmentioning
confidence: 96%
“…Additionally, Chen et al (181) found that tumor cells expressing CD38, which regulates the adenosine production pathway, escape from checkpoint inhibitor-mediated immune attack. In patients with advanced melanoma, resistance to PD-1 blockade therapy was reported to be linked to genetic aberrations in the cyclin D–cyclin-dependent kinase 4 (CDK4) pathway (182). Moreover, anti-PD-1 antibody binding to Fc receptors expressed on tumor-associated macrophages can partially be removed from tumors, which may reduce the effect of PD-1 antibodies (183).…”
Section: Resistance To and Toxicity Of Pd-1/pd-l1 Inhibitorsmentioning
confidence: 99%
“…Three out of five patients presented with CCND1 amplification ( 5 ). A retrospective study of melanoma also showed that 30 out of 56 patients with innate resistance to anti-PD-1 therapy presented with CCND1 amplification ( 6 ). Although there are currently few reported cases, the clinical phenomena suggest the potential value of CCND1 amplification as a biomarker for predicting negative therapeutic effects of ICIs.…”
Section: Introductionmentioning
confidence: 99%